2017
DOI: 10.1097/sla.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Technical Performance on Patient Outcomes in Surgery

Abstract: The results of this systematic review demonstrated that superior technical performance positively affects patient outcomes. Despite this initial evidence, more robust research is needed to directly assess intraoperative technical performance and its effect on postoperative patient outcomes using meaningful assessment instruments and reliable processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 63 publications
0
52
1
Order By: Relevance
“…A successful surgical outcome is the result of many individual, team and organizational factors. At the same time, there is emerging evidence emphasizing the importance of both technical and non‐technical performance. Reports have indicated that most errors in the operating theatre are technical in nature, and technical performance may affect patient outcomes more than the perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…A successful surgical outcome is the result of many individual, team and organizational factors. At the same time, there is emerging evidence emphasizing the importance of both technical and non‐technical performance. Reports have indicated that most errors in the operating theatre are technical in nature, and technical performance may affect patient outcomes more than the perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…Therein lies a dichotomy, where increasing reliance now exists on fellowship training to bridge the shortfall in experience that is largely caused by changes in postgraduate surgical training and the well documented global reduction in working and training hours [34][35][36][37][38][39][40] . Changing training from a time-based to a competency-based system does not overcome such working time restrictions 41,42 and therefore explains the subsequent shift in training philosophy to that of proficiency-based models [43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, the improved surgical conditions in the narrow space of retroperitoneal laparoscopic surgery during high-dose rocuronium NMB contribute to superior technical performance of the surgeon and less trauma to tissue. A recent review supports this hypothesis by concluding that superior technical performance positively affects patient outcome [ 29 ]. An important reason for readmission was an infectious complication of the urinary tract (complicated urinary tract infection including pyelonephritis and urosepsis).…”
Section: Discussionmentioning
confidence: 93%